Species, performance and sex ratio of shark landed in Pelabuhan Perikanan Samudra Cilacap - Dian Bhagawati; Tri Nurani; Muh. Nadjmi Abulias (Jurnal Iktiologi Indonesia, 2017)
Shark fisheries in Indonesia are still relying on the natural catch. Several shark species are important fisheries commo-dities and are highly collected. Although there are several rules to control catch, usage, and conservation status, in practice, fishermen are less submissive. This study was conducted to obtain information about species diversity, per-formance, and sex ratio of sharks which were found in Cilacap Port in October to November 2015. The method used was purposive random sampling technique. Samples were taken four times with two weeks interval for each observation. The parameters were species number, total body length, body weight, morphometry and sex. Data were analyzed descriptively. Thirty six sharks were recorded during the sampling which consisted of 14 species. Among 36 individuals, 7 individuals were juveniles, 3 individuals were adolescence, and 26 individuals were adults. Alopias superciliosus (321 cm) was the longest species, while the shortest was Sphyrna lewini (59 cm); Isurus oxyrinchus was the heaviest (100 kg) species and the lightest species was Carcharhinus falciformis (1 kg). In general, female fish were obtained more than the males. Abstrak Produksi ikan hiu di Indonesia masih mengandalkan hasil tangkapan dari alam. Meskipun sudah terdapat beberapa per-aturan yang mengatur tentang penangkapan, pemanfaatan dan status perlindungannya, namun dalam prakteknya kurang dipatuhi. Penelitian ini dilakukan untuk mendapatkan informasi tentang keragaman spesies, performa, dan nisbah kela-min ikan hiu yang didaratkan di Pelabuhan Perikanan Samudra Cilacap pada periode Oktober sampai dengan November 2015. Sampel dipilih dengan persyaratan tertentu dan identifikasi dengan teknik photo ID (Photo-Identiûcation). Para-meter yang diamati adalah jumlah jenis, panjang total, bobot tubuh, morfometrik, dan jenis kelamin. Data yang diper-oleh dianalisis secara deskriptif. Selama pengambilan sampel diperoleh 36 ekor ikan hiu, yang terdiri atas 14 jenis, dan tergolong yuwana sebanyak 7 ekor, 3 remaja, dan 26 dewasa. Ikan yang tertangkap dan memiliki ukuran tubuh terpan-jang adalah Alopias superciliosus (321cm), terpendek Sphyrna lewini (59cm); terberat Isurus oxyrinchus (100kg) dan teringan adalah Carcharhinus falciformis (1kg). Secara umum ikan betina lebih banyak tertangkap daripada ikan jantan.